49 Outcome after Adult Heart Transplantation following Failure of Atrial Switch Procedure. (6th June 2015) - Duong, Phuoc; Parry, Gareth; O'Sullivan, John; Crossland, David; Hasan, Asif
Abstract : Objective: To investigate the outcome of orthotopic heart transplant (OHT) in adult population for failing atrial switch operation in childhood. Methods: Between 2001 and March 2013, 230 OHT were performed at our institution. Of these twenty patients (8.7%) had undergone previous atrial inversion procedures (7 Senning, 13 Mustard) for simple Transposition of Great Arteries (TGA) or TGA with ventricular septal defect (VSD) Mean age of atrial switch procedure was 22.9 ± 24.3 months. Two patients were mechanically supported to OHT with Heartware HVAD. Mean age at OHT was 27.2 ± 9.6 years, medium time from atrial switch was 25.3 years. Donor ischaemic time and CPB were 192.4 ± 50 and 207.2 ± 88.5 min respectively. Lenght of stay in ITU was 6.5 days (1–25 days). Four patients required renal replacement therapy (CVVH) and one needed tracheostomy. Median follow up is 4.7 ± 3.6 years. Five deaths occurred (25%): 3 early deaths (one cerebro-vascular accident and 2 acute rejections), 2 late deaths (a EBV-related lymphoproliferative disorder and a late rejection). All deaths occurred before 2003. Conclusions: Heart transplantation in patients with failing systemic ventricle following atrial switch procedure is associated with a medium and long term good outcome in the modern era. However the recent development of mechanical cardiac support has allowed us to bridge more efficiently these patients to OHT with better selection of donors and improved outcome.